2019
DOI: 10.1002/esp.4636
|View full text |Cite
|
Sign up to set email alerts
|

Temporal and spatial variation of soil erosion in wooded rangelands of southwest Spain

Abstract: Changes in land use are common in Mediterranean areas and are reported as having produced changes in the intensity of soil erosion. Dehesas are rangelands with a disperse tree cover, widespread in the south-western part of the Iberian Peninsula and similar ecosystems are also common in other areas with a Mediterranean climate. The aim of the present study is to analyse temporal and spatial variations of soil erosion rates estimated along three hillsides, located in two farms (Buitrera and Parapuños) in southwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 56 publications
0
6
0
Order By: Relevance
“…Land use and land cover (LULC) play a critical role in soil erosion processes. The changes in LULC can have significant effect on susceptibility to soil erosion [23][24][25], especially in case of agricultural land use [26][27][28], and, thus, can contribute to reductions in soil organic carbon (SOC) [29]. Therefore, understanding LULC dynamics and its effects on soil erosion can provide key information to decision makers [11,[30][31][32][33].…”
Section: Introductionmentioning
confidence: 99%
“…Land use and land cover (LULC) play a critical role in soil erosion processes. The changes in LULC can have significant effect on susceptibility to soil erosion [23][24][25], especially in case of agricultural land use [26][27][28], and, thus, can contribute to reductions in soil organic carbon (SOC) [29]. Therefore, understanding LULC dynamics and its effects on soil erosion can provide key information to decision makers [11,[30][31][32][33].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, soil erosion is more than the loss of sediments as it also poses risks to human societies [6,7]. Understanding which factors play key roles in runoff generation and subsequent soil loss is crucial to the design of proper land management plans [8,9]. Despite the huge amount of studies published in the last decades, the contribution of each of the factors governing the soil erosion process is still not clear [6,10].…”
Section: Introductionmentioning
confidence: 99%
“…(2010) argued that soil erosion‐induced lateral fluxes of N and P are of similar magnitude to those induced by fertilizer application and crop removal. Nevertheless, current studies almost exclusively attribute the variability of soil C, N and P within sloping farmland to water erosion, while less attention has been paid to the role of tillage erosion (Hu et al., 2020; Q. Y. Li et al., 2014; Rubio‐Delgado et al., 2019; Shi & Schulin, 2018; Thaler et al., 2021). Tillage erosion, defined as the net translocation of soil material by tillage operations, typically results in soil loss from slope convexities and soil accumulation in slope concavities (Lobb et al., 1999; Quine et al., 1997).…”
Section: Introductionmentioning
confidence: 99%
“…Failure to recognize tillage erosion reflects its almost invisible nature on a per‐event basis (FAO, 2019). However, recent studies have shown that the effect of tillage erosion on soil degradation is even more important than water erosion (Öttl et al., 2021; Rubio‐Delgado et al., 2019; Thaler et al., 2021; Zhao et al., 2018). For example, more than one‐third of the Corn Belt in the midwestern United States has completely lost its C‐rich topsoil, largely attributed to tillage erosion, which reduces corn ( Zea mays L.) and soybean [ Glycine max (L.) Merr.]…”
Section: Introductionmentioning
confidence: 99%